From the white darkness to dark tourism: the case of Sarikamish. Issue 3 (1st August 2016) - Yirik, Sevket; Seyitoğlu, Faruk; Çakar, Kadir
Abstract : Purpose: The purpose of this paper is to understand and examine whether the Sarikamish battlefield site can be considered as a dark tourist attraction by exploring the extent to which the site meets the five stages of MacCannell's sacralisation process. Design/methodology/approach: In the present research, the case study approach was adopted within the context of the battlefield site to examine the sight sacralisation concept, which is credited to MacCannell (1976), by considering its five stages, which include naming, framing and elevation, enshrinement, mechanical reproduction and social reproduction. Findings: The findings of the present study reveal that the Sarikamish battlefield site has the potential for dark tourism consumption. However, there is lack of interest in the Sarikamish site, and little attention has been paid to this issue. The results also show that there is a significant difference between the Gallipoli and Sarikamish battlefields in terms of tourist flows regarding dark tourism. Research limitations/implications: Because of time limits and the long distance to the Sarikamish province, this research benefited from gathering data both from printed documents and websites related to the province, in addition to interviews that were conducted using semi-structured questions, which were e-mailed to the respondents. Originality/value: The present study is unique in regards to its objective, which is to increase public awareness about the site. Moreover, it seeks to make people more cognisant in terms of motivation to visit the Sarikamish battlefield, and these issues have been given little attention by scholars.